Spermatogenesis and gonadal cycle in male Tamoya haplonema and Chiropsalmus quadrumanus (Cnidaria, Cubozoa) - Tiseo, Gisele R.; García-Rodríguez, Jimena; Zara, Fernando J. [UNESP]; Ames, Cheryl Lewis; Marques, Antonio C.; Morandini, André C. (Elsevier, 2019)
Spermatogenesis has been little studied in cubozoans. This work describes spermatogenesis of two cubozoan species from Brazil, Tamoya haplonema and Chiropsalmus quadrumanus, using light microscopy and histochemical techniques to highlight and contrast stages of the gonadal cycle. Specimens were collected by hand at the water surface or with shrimp trawls in three areas in the state of São Paulo (SE Brazil): Cananéia lagoon estuarine system (south), Santos and São Vicente Bay (central), and São Sebastião and Ubatuba (north). Male box jellyfish gonads are located between the mesoglea and gastrodermis in a thin and independent layer, organized in elongated follicles, macroscopically resembling a fingerprint pattern. After subsampling, serial sections were performed on male gonad tissue. The resulting slides were stained with hematoxylin and eosin and methods for staining proteins, acidic materials and neutral polysaccharides. Light microscopy revealed that the follicle wall of the male gonads of both cubozoan species is composed of spermatogonia. Spermatocytes are found peripherally near the follicle wall, while spermatids and spermatozoa are located towards the center. Sperm release occurs through rupture of the follicular wall into the gastric pockets. Four stages of gonad development were documented for T. haplonema and three for C. quadrumanus. The sperm of C. quadrumanus has a rounded head while in T. haplonema the sperm head is conical with an elongated apical projection. In both species, there was no positive histochemical reaction for putative acrosomal vesicles precursors.
Keywords: Acrosomal vesicle; Box jellyfish; Gonad; Histochemistry; Histology; Sperm